Anticorpos naturais e infecção: anticorpos naturais na doença de Chagas e na paracoccidioidomicose - Unterkircher, Carmelinda Schmidt [UNESP] (Universidade Estadual Paulista (Unesp), 1994)
Using ELISA technique, natural antibodies against self and non self antigens were determined in 80 patients chronically intected by T. cruzi and 40 individuals suffering from a deep mycosis frequentely found in Latin Amarica (Paracoccidioidomycosis - PCM). Two forms of PCM were investigated: adult forms and juvenil type of disease. Eighty percent (80%) of the former group had significantly elevated anti-laminin antibody levels (M=4.7,SD±1.8) compared with healthy controls and different specificities of antibody were associated with anti-laminin in pathological sera. A notable binding to cytoskeletal proteins was observed, specially with band 3 and their peptides derivates, such as 62 kDa peptide. By means of Protein A chromatography we were able to show that natural anti-Gal antibodies may be bound by their Fab region to other immunoglobulins and/or to Protein A by alternative sites of binding. The finding of lgG anti-Gal antibodies in circulating immune complexes isolated from chagasic sera supported the first alternative. However, it is possible that some of lgG anti-Gal antibodies, belong to VH111 subgroup of immunoglobulins, that bind directly to Protein A. Among the 40 sera from PCM examined, the majority was considered as not exhibiting a signilicantly higher binding than normal sera to antigens tested. However thirty percent (30%) of the chronic patients had an increased levels of natural antibodies at least for one specificity such as actyn, myosin and Gala1,3Gal epitopes. ln juvenil type of PCM the mean value found for actyn was also increased 2,42 (range 1,0 to 5,3). Utilizing the polyethylene glicol precipitation the presence of circulating immune complexes was investigated in PCM sera. Specific antibodies for soluble antigens from P. brasiliensis and natural antibodies against myoglobin, myosin and Gala1,3 Gal epitopes were characterized

Anticorpos naturais para antígenos próprios e exógenos foram analisados pela técnica de ELISA, em 60 soros de pacientes cronicamente infectados pelo T. cruzi e, em 40 soros de indivíduos sofrendo de uma micose profunda, freqüentemente encontrada na América Latina (Paracoccidioimicose). Cerca de 80% dos indivíduos do primeiro grupo tinham níveis significativamente elevados de anticorpos antilaminina (M=4,75, DP±1,88) quando comparados com os controles saudáveis e, diferentes especificidades de anticorpos estavam associadas com antilaminina nos soros chagásicos. Foram observados anticorpos reativos com as proteínas do citoesqueleto, especialmente com a banda 3 e seus peptídeos, como o de 62 kDa. Por meio de cromatografia, em Proteína-A - Sepharose, mostramos que uma parte significante do antiGal natural pode estar ligada por sua região Fab a outra molécula de imunoglobulina e/ou a sítios alternativos de ligação na Proteína A. O achado de lgG antiGal nos imunocomplexos reforçam a primeira hipótese. Todavia, é possível que algumas lgG aniiGal pertençam ao subgrupo VH111 de imunoglobulinas. Entre os 40 soros de PCM examinados, a maioria tinha níveis normais de anticorpos naturais. Todavia, 30% dos pacientes crônicos apresentavam aumentos de pelo menos uma especificidade de anticorpo natural, tal como antiactina, antimiosina e antiGal. Na forma juvenil os anticorpos antiactina estavam aumentados de 2,4 vezes (1,9 a 5,3 vezes), sugerindo uma associação com a doença disseminada. lmunocomplexos foram pesquisados nos soros de PCM utilizando a técnica de precipitação com polietileno glicol 6000. Nos imunocomplexos Isolados foram encontrados principalmente anticorpos específicos para antígenos solúveis de P. brasiliensis
Keywords: Chagas, Doença de; Paracoccidioidomicose; Antigenos; Antigens